Chronic Central Serous Chorioretinopathy in a Patient with Pigment Dispersion Syndrome: A Possible Correlation - Dimitrios Kourkoutas; George Tsakonas; Aristotelis Karamaounas; Nikolaos Karamaounas (Case Reports in Ophthalmological Medicine)
Chronic central serous chorioretinopathy (CSCR) is a progressive chorioretinopathy with widespread atrophic RPE abnormalities and serous retinal detachments (SRDs) present for 6 months or longer. We report a case of CSCR in a 38-year-old patient with Pigment Dispersion Syndrome (PDS). In the presented case of CSCR, the chronic course of the disease may in part be associated with an underlying generalized degenerative dysfunction of the pigmented cells of the eye on grounds of PDS. We suggest that a chronic course of disease may be suspected in the setting of CSCR with concurrent RPE pathology, such as what is found in PDS.